WA2MA: A model-driven approach for reengineering web applications into mobile applications - Khiati, Nadri; Bouchiha, Djelloul; Atig, Yahia; Hacene, Sofiane Boukli (Edelweiss Applied Science and Technology, 2025)
With the increasing prevalence of mobile computing, organizations must adapt legacy web applications to pervasive information systems, ensuring seamless accessibility across diverse devices. This paper introduces WA2MA, a model-driven reengineering approach for systematically transforming web applications into mobile applications. The approach follows a structured three-phase process based on Model-Driven Architecture (MDA) principles: Reverse Engineering, where Platform-Independent Models (PIMs) are extracted to represent the structural and behavioral aspects of the existing web application; Transformation, where these models are refined into Platform-Specific Models (PSMs) using a tailored Unified Modeling Language (UML) profile to address mobile platform constraints; and Forward Engineering, where automated model-to-text transformations generate a significant portion of the mobile application’s source code. The Acceleo technology is leveraged to facilitate this automation through predefined transformation rules and code generation templates. A case study demonstrates the effectiveness of the WA2MA approach, highlighting a substantial reduction in manual effort and improved consistency in the generated code. This research contributes to the advancement of model-driven engineering (MDE) by providing a structured and scalable methodology for the migration of web applications to mobile platforms.